Is Love a “pathological condition of the soul”? Joyce Carol Oates's Beasts and Rape: A Love Story - Nicolas P. Boileau (Bearing Witness: Joyce Carol Oates Studies)
This paper seeks to address the question of Oates’s relation to feminist and gender theories by looking at two novellas published consecutively, Beasts and Rape: A Love Story in the beginning of the 2000s. The short texts share a common storyline based on rape, which is far from uncommon in Oates’s fiction. However, I argue that there is something very specific in these two novellas in the way Oates chooses to handle the testimony of the rape, both overtly and covertly, both in graphic details and in repressed forms of expression, giving way to a reflection on women’s vulnerable position within the symbolic order as defined by psychoanalysis. The Modernist tropes referred to, together with Oates’s glimpse at psychoanalytic theory at a time when approaches to rape would have been predominantly based on trauma theory, contribute to making these two texts fascinating examples of Oates’s trying to rewrite the “rape script”, and therefore challenge it.